Diversity and Community Structure of Oribatid Mites (Acari, Oribatei) at Memorial Complexes of a Megapolis - Kolodochka, L.A.; Shevchenko, O.S. (Вестник зоологии, 2013)
In different types of substrate (soil, litter, lichens and mosses) collected at three memorial complexes (cemeteries) of Kyiv (Ukraine), 70 species from 57 genera, 34 families of oribatid mites were found. A few eurytopic species capable of tolerance to different types of pollution make up an essential part in each species complex. The species diversity and complexity of oribatid community structure at researched areas increased with distance from the city center. There was no direct relation between the degree of dominance of most common species and the cemetery’s relative remoteness from the center of the city. Установлено, что в почвах, подстилке, мхах и лишайниках на территории трех мемориальных комплексов (кладбищ) г. Киева (Украина) обитают 70 видов 57 родов 34 семейств клещей-орибатид (Acari, Oribatei). Основу видовых комплексов составляют эвритопные виды, устойчивые к разнообразным типам загрязнения среды. Видовое разнообразие и сложность структуры сообществ клещей-орибатид обследованных территорий увеличиваются от центра города к окраине. Непосредственная связь степени доминирования наиболее массовых видов с удаленностью от центра города не установлена.